Labor Force Participation in the Older Cohort: Easing Social Security Deficits at the Margins - Michael Lumley (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
This paper examines possible avenues to salvage national retirement programs. It first proposes changes to the system which would in theory entice Americans to remain in the work force at older ages, such as adjusting the retirement age, expanding the Average Indexed Monthly Earnings calculation base, establishing a ‘paid-up’ category for payroll taxes, establishing Medicare as the primary payer for working seniors, and reducing or eliminating regulations that prevent men and women from gradually retiring. The paper then turns to look at the effect of policy changes on labor force participation. The data is processed with an Ordinary Least Squares estimator. The results of the eight regressions were mixed, and are discussed in detail within the paper.
Keywords: Undergraduate Research; Pursuit